The Effect of Internal Control Factors on the Accountability of the Auditor at the Inspectirate of Jombang District (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2017)
Government Regulation Number 60 of 2008 on Government Internal Control System is a manifestation of government commitment in order to improve the performance, transparency and accountability of state finance management and to clarify the role of internal control. This study aims at testing and analyzing the influence of internal control factors to auditors who work in the inspectorate of Jombang District. The population in this study are all auditors working in Jombang inspectorate which amounted to 35 auditors. The research sampling uses census method with unit of analysis as many as 35 auditors at Inspectorate of Jombang District. The type of this research is quantitative research using multivariate statistical analysis by using multiple regression analysis. The tests used are validity, reliability, and hypothesis testing. The result of the research proves that controll environment, management risk assessment, activity control, communication and information, and monitoring affect on auditor accountability in the Inspectorate of Jombang District. Based on the results and discussion of the research, the conclusion that can be taken is the auditor at the Inspectorate of Jombang District should pay attention and keep the compliance of internal control because it will make auditor accountability awake.